Association between RsFT, RsFLC and RsCOL5 (A&B) expression and flowering regulation in Japanese wild radish. Issue 4 (23rd June 2021) - Han, Qingxiang; Sakaguchi, Shota; Wakabayashi, Tomomi; Setoguchi, Hiroaki
Abstract: Flowering is an important step in the life cycle of plants and indicates adaptability to external climatic cues such as temperature and photoperiod. We investigated the expression patterns of core genes related to flowering-time regulation in Japanese wild radish ( Raphanus sativus var. raphanistroides ) with different vernalization requirements (obligate and facultative) and further identified climatic cues that may act as natural selective forces. Specifically, we analysed flowering-time variation under different cold and photoperiod treatments in Japanese wild radish collected from the Hokkaido (northern lineage) and Okinawa (southern lineage) islands, which experience contrasting climatic cues. The cultivation experiment verified the obligate and facultative vernalization requirements of the northern and southern wild radish accessions, respectively. The expression of major genes involved in flowering time indicated that RsFLC and RsCOL 5 ( A & B ) may interact to regulate flowering time. Notably, floral initiation in the northern lineage was strongly correlated with RsFLC expression, whereas flowering in the southern linage was correlated with induction of RsCOL5-A expression, despite high RsFLC transcript levels. These results suggested that the northern accessions are more sensitive to prolonged cold exposure, whereas the southern accessions are more sensitive to photoperiod. These different mechanisms ultimately confer an optimal flowering time in natural populations in response to locally contrasting climatic cues. This study provides new insights into the variant mechanisms underlying floral pathways in Japanese wild radish from different geographic locations. Abstract : To identify climate cues that might act as natural selective forces shaping the genetic variation for flowering initiation, we conducted analyses of the flowering-time variation in response to cold treatment and day length in wild radish collected from Hokkaido and Okinawa islands with vernalization requirements. Our results collectively offer a hint that accessions with obligate vernalization requirements might exhibit a higher sensitivity to prolonged cold exposure, whereas in accessions with facultative vernalization requirements the photoperiod pathway predominates, and these mechanisms confer an optimal flowering time in natural populations, in response to their contrasting climate cues.